PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN INVESTASI INVESTOR PEMULA - Sefvira Maharani; Putri Ayu Amelia; Ahmad Wahyudi Zein (INTERNATIONAL, Journal of Sharia Business Management, 2026)
Social media is a frequently used method by novice investors to learn about various types of investments, obtain advice, and stay abreast of changes in the financial markets. This study was conducted to understand how social media influences novice investors' investment decisions. The method used was qualitative research with a descriptive approach, using interviews and reading various written sources. This study shows that social media plays a significant role in helping novice investors make investment decisions. Information obtained from learning materials, investor experiences, and advice from financial influencers can increase someone's interest and confidence in investing. However, information circulating on social media is not always accurate, so investors must verify and analyze it before deciding to invest. Therefore, the ability to filter information is crucial for more accurate investment decisions and align with financial goals. This study is expected to shed light on the role of social media in helping novice investors make investment decisions.